Junk Food and Food Insecurity in Developing Countries - Neupane, Dipika (Health for All, 2015)
Rapid population growth and urbanization is increasing challenges to maintain food security. In this context, large multinational companies are coming forward to supply food to the whole world. They are supplying junk food items that have attractive packaging and good taste with very low nutritive value. These foods are getting popular due to time factor, taste factor and appealing advertisements. Specially, school aged children are getting addicted to these foods which is hampering their growth and development and are being vulnerable to non-communicable diseases. In developing countries, this has added double burden of disease creating new challenge to the health system. This increasing popularity is due to globalization and market liberalization in food marketing. To control its consumption, huge capital expenditure in food marketing and false advertisement should be restricted. Meanwhile, effective health promotion activities will help to create awareness about dietary needs among general population. Health for All Vol.2 2014: 6-8